The role of oral microbiota in cancer - Lan, Zhou; Liu, Wei-Jia; Cui, Hao; Zou, Ke-Long; Chen, Hao; Zhao, Yu-Yue; Yu, Guang-Tao (Frontiers in Microbiology, 2023)
Cancer remains a significant global challenge, with an estimated 47% increase in cancer patients from 2020 to 2040. Increasing research has identified microorganism as a risk factor for cancer development. The oral cavity, second only to the colon, harbors more than 700 bacterial species and serves as a crucial microbial habitat. Although numerous epidemiological studies have reported associations between oral microorganisms and major systemic tumors, the relationship between oral microorganisms and cancers remains largely unclear. Current research primarily focuses on respiratory and digestive system tumors due to their anatomical proximity to the oral cavity. The relevant mechanism research mainly involves 47% dominant oral microbial population that can be cultured in vitro. However, further exploration is necessary to elucidate the mechanisms underlying the association between oral microbiota and tumors. This review systematically summarizes the reported correlations between oral microbiota and common cancers while also outlining potential mechanisms that may guide biological tumor treatment.